THE MIGRATION OF TIRUNELVELI TAMIL CHRISTIANS TO MALAYA AND THEIR WEDDING TRADITIONS IN MALAYSIA - Samuel, SamikkanuJabamoney Ishak (International Journal of Psychosocial Rehabilitation, 2020)
The major objective of the research is to explain the migration of Tirunelveli Tamil Christian to Malaya and their wedding traditions in Malaysia. Qualitative approach was used for this study. The two methods such as field work and table work were used for this study. In the table work, research thesis, books and research articles were selected and the data from these were analyzed using descriptive approach. Moreover, for the field work, the researcher had collected data by attending Tirunelveli Tamil Christian marriage functions and had relied on hisown personal experiences The findings show that in the early 20th century, a sizeable number of converted Tirunelveli Tamil Christians had migrated in families to Malaya to start their own small businesses. Today they live in groups in the Malaysian cities of Ipoh, Kuala Lumpur and Penang. This diaspora of Tirunelveli Tamil Christians brought along their traditions and culture as well. Even though these Tirunelveli Tamils were converted into Christianity, they adapted their original traditions and culture to that of Christianity. As a matter of fact, the marriage patterns of Tirunelveli Tamil Christians have similarities tothe marriages that were practiced during the Tamil Sangam and Medieval Period. This study is useful in finding out the pattern of migration of Tirunelveli Tamil Christians to Malaya and their wedding traditions that are still in practice in Malaysia. The research claims to be the first such attempt to do a study regarding the migration of Tirunelveli Tamil Christians to Malaya and their wedding traditions that are still in practice in Malaysia.